ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN YANG TERDAFTAR DI BEI (Studi Empiris pada Seluruh Perusahaan yang Terdaftar di Bursa Efek Indonesia 2009-2011) - Miswandi '; Emrinaldi Nur Dp; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study is aimed to examine the factors that influence the dividend payout ratio (DPR) on companies listed in Indonesian Exchange. These factors, such as return on equity, cash position, debt to equity ratio, degree of operating leverage, and taxe rate. The population is all of company listed on the Indonesia Stock Exchange in 2009-2011. With purposive sampling technique obtained a total of 82 companies in the sample of total population 464 companies. Types of data using secondary data from financial statements. Data analysis method used is multiple regression analysis with the help of software SPSS version 17 (Statistical Product and Service Solution version 17). The test data used is a partial hypothesis test (t), simultaneous hypothesis testing (f), and the coefficient of determination (R2). The results show that of the five hypothesis proposed, only three variables have influence of dividend payout ratio, its return on equity (sig = 0.095), cash position (sig = 0.020) dan debt to equity ratio (sig = 0.008). while two other variables is degree of operating leverage (sig = 0.748) dan taxe rate (sig = 0.166) doesn’t have influence of dividend payout ratio. Based on the test result of the coefficient determination, the value of the Adjust R Square is 12.9% while the remaining 87.1% is influenced by other variables that are not included in this study.Keywords: Return on Equity, Cash Position, Debt to Equity Ratio, Degree of Operating Leverage, Taxe Rate and Dividend Payout Ratio